Reduced Graphene Oxide on Activated Carbon-Manganese Dioxide Composite Materials for High-Performance Supercapacitor Electrodes - Adinandra Caesar Fachrudin; Harsojo Sabarman (NBRI Press, 2023)
This study presents the addition of reduced graphene oxide (rGO) on the surface of activated carbon-manganese dioxide (ACMnO2) composite material via high-temperature variations of 350 to 450 °C to increase the specific capacitance of the ACMnO2/rGO composite electrode. The composite material is synthesized by coating the slurry mixture on the aluminum sheet using a 2-step doctor blade method with polyvinylidene difluoride (PVDF) material and dimethylformamide (DMF) solution as a binder. Then symmetric supercapacitor is fabricated using filter paper as a separator and 3M potassium hydroxide (KOH) solution as an electrolyte. The composite material analysis is characterized by X-ray diffraction (XRD) and scanning electron microscope (SEM) as well as cyclic voltammetry (CV) for the electrochemical properties. The ACMnO2/rGO composite electrode at a temperature variation of 350 °C showed the highest specific capacitance of 459.79 F g-1 at a scan rate of 9 mV s-1 with an energy density of 63.859 Wh kg-1. The addition of rGO on the surface of the ACMnO2 composite material increased the specific capacitance by about 58% compared to without rGO, showing promises for high-performance supercapacitor electrodes.